Dampak Kecerdasan Emosional Pada Prestasi Akademik Mahasiswa Di Fakultas Manajemen Ekonomi - Heppy Lestari; Wahyu Imellya (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to explore the impact of emotional intelligence on student academic achievement at the Faculty of Economic Management. Using a quantitative approach, data was collected through questionnaires and analyzed to evaluate the relationship between emotional intelligence and academic achievement. It is hoped that the results of this research will provide useful insights for educational practitioners in improving the quality of learning within the Faculty of Economic Management.